Efficient Oxygen Evolution Electrocatalyst by Incorporation of Nickel into Nanoscale Dicobalt Boride. Issue 7 (19th March 2021) - Schuch, Jona; Klemenz, Sebastian; Schuldt, Patrick; Zieschang, Anne‐Marie; Dolique, Stephanie; Connor, Paula; Kaiser, Bernhard; Kramm, Ulrike I.; Albert, Barbara; Jaegermann, Wolfram
Abstract: Recently, transition metal borides attracted increased attention as electrocatalysts for the oxygen evolution reaction. Here, we show how the incorporation of nickel into nanoscale dicobalt boride results in an improvement of the activity and stability of the catalyst in alkaline electrolytes. The borides are obtained by a one‐step solution synthesis, calcined, and characterized by X‐ray diffraction and scanning electron microscopy. For (Co1‐x Nix )2 B (x=0, 0.1, 0.2, 0.3, 0.4, and 0.5), (Co0.9 Ni0.1 )2 B shows the best performance with an overpotential of η=371 mV at 10 mA cm −2 in 1 M KOH. Normalization to the electrochemical surface area shows a clear dependence on the activity with rising nickel content. X‐ray photoelectron spectroscopy reveals that the catalyst is modified under reaction conditions and indicates that CoOOH and Ni(OH)2 are formed as active surface species. Flame atomic absorption spectroscopy (F‐AAS) measurements show that no cobalt is dissolved during the electrochemical investigations, but the nickel concentration is increased on the surface of the catalyst as follows from XPS measurements after the electrochemical investigation. Abstract : Nickel (re)adsorption from electrolyte: X‐ray photoelectron spectroscopy was used to investigate the surface composition of nanocrystalline (Co, Ni)2 B after electrochemical activation and investigation as OER catalyst. The particles form an oxide layer of changing composition: boron oxide after synthesis, OER‐active CoOOH and Ni(OH)2 after activation with an increase of Ni‐species after investigation. The additional Ni is (re)adsorbed from the electrolyte during the electrochemical treatment.